Art and Knowledge - Etuk, Anthony Raphael; Ette, Emmanuel E. (NIU Journal of Humanities, 2025)
The question of whether art can provide humans with knowledge remains a subject of sharpest controversy among philosophers, artists, and art critics over time. The controversy is no less complicated now than it was historically, nor is it any closer to being resolved. Recent objection to art’s epistemic value maintains the basic line of reasoning that art lacks propositional contents in the sense of propositional knowledge – since works of art do not typically express, clear, explicit propositions in the way that language does. More than ever, this tends to render the epistemic value of art highly questionable. However, a contrary line of response in defense of art’s epistemic value involves identifying some other epistemic aims, and showing how art’s conduciveness to them justifies its epistemic value. Identifying with this approach, I argue in this paper for the epistemic value of art. Drawing upon Nelson Goodman’s Art-symbol-theoretic, I argue that although art may not always provide factual knowledge (in a propositional sense), yet, through its symbolic nature, art is capable of conveying ideas and experiences in a way that shapes our understanding of the world – where, besides knowledge, understanding is here identified as an epistemic aim. Keywords: Art, Epistemic Aims, Understanding, Nelson Goodman, Knowledge.